PETTY TRADING AND RURAL ECONOMICS: A STUDY OF AKOKWA TOWN, IDEATO NORTH, LGA IN IMO STATE, NIGERIA - Anyaoha, Okechukwu; Odum, Chinemerem Jennifer (African Journal of Social and Behavioural Sciences, 2024)
This survey study examined the impact of petty trading on improving the socioeconomic status of the rural dwellers of Akokwa community in Ideato North L.G.A of Imo State. The sample was made of 323 respondents who were selected randomly. Hypotheses were formulated to guide the study. Open-ended and close- ended used for data collection. The data gathered were analysed using the Chi-Square statistics. Findings revealed a significant relationship between petty trading and both income level and standard of living among rural dwellers in Akokwa Community. Specifically, the chi-square analysis demonstrated that petty trading positively influenced income levels (χ2 = 7.2, p < 0.05) and led to an improved standard of living among rural dwellers in Akokwa Community (χ2 = 7.5, p < 0.05). These findings emphasise the important roles of petty trading as a means of income generation and economic empowerment in rural areas. The study therefore, recommended that the government should provide easy access to microfinance institutions or schemes that could offer low-interest loans to petty traders. Training programs and workshops should be provided to petty traders by the government and non-governmental organization to improve their business skills and financial management.